FACTORS INFLUENCNG THE ADOPTION OF COCOYAM TUBERS ENTERPRISES AMONG YOUTH IN SOUTH EASTERN NIGERIA - Madu, V. U.; Abu, I. A.; Mohammad, I.; Atman, F. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined the factors influencing the adoption of cocoyam enterprise among youth in Southeast Nigeria. Multistage sampling technique was used in selecting 437 respondents. Data were collected using structured questionnaire and analyzed using both descriptive and inferential statistics. The result revealed that majority (66.6% and 66.8%) of the respondents were male and married, respectively. Similarly, 40.0% of the respondents had secondary education with mean age, household size, and farm size of 29.6 years, 3 persons and 1.92 ha, respectively. The result also revealed that majority (60.0%, 54.2%, and 51.0%) of the respondents received information on cocoyam enterprises through extension agents, research officers and radio/television which were ranked 1st, 2nd, and 3rd, respectively. Half (50.1%) of the respondents had high level of adoption of the cocoyam enterprise while 19.2% have a very high level of adoption. The results of regression analysis of factors influencing the adoption of cocoyam enterprise revealed that age (P< 0.05), household size (P< 0.1), membership of cooperative (P< 0.01) and contact with extension agents (P< 0.05) significantly influenced the adoption of cocoyam enterprise in the study area. The major constraints to the adoption of cocoyam enterprise in the study area were inadequate access to credit facilities, high cost of inputs, and weed infestation, which were ranked 1st, 2nd, and 3rd, respectively. It was concluded that age, household size, membership of cooperative and contact with extension agents significantly influenced the adoption of cocoyam enterprise in the study area. The study recommended that Government and stakeholders should implement affordable and subsidized loan programmes specifically for young cocoyam farmers, there should be advocacy for land reforms and government-supported land leasing programs is needed to improve young farmers’ access to agricultural land and farmers should be encourage to form and join cooperatives in order to enjoy economies of scale.